Likelihood of Arrest for Robberies, Assaults, and Sexual Offenses Committed by Group and Lone Offenders - Terranova, Victoria A. (Journal of interpersonal violence, 2021)
Many criminologists have considered the role of groups in the commission of crime to gain insight into offender decision-making. Additional research is needed, however, that examines the likelihood of arrest as a function of whether an offense is committed by a group of offenders (two or more offenders in a criminal incident) or a lone offender, as well as the number of offenders in the group. Using 3 years of data from the National Incident-Based Reporting System for robbery incidents, assault incidents, and sexual offenses, the study finds that the relative likelihood of arrest for group-offender incidents, compared with lone-offender incidents, varies by incident type. For robbery incidents, the likelihood of arrest increases when committed by a group of offenders. Yet, for assault incidents and sexual offenses, the likelihood of arrest decreases when committed by a group of offenders. Further analysis looks more closely at incidents committed by a group of offenders and how the number of offenders in the group affects the likelihood of arrest. A consistent finding is that for each incident type, the likelihood that all offenders in a group will be arrested is lower as the number of offenders increases, which may justify offenders’ perceptions of “safety in larger numbers.”